Educação infantil: retrato de uma rede municipal de ensino - Henriques, Afonso Canella (Universidade Federal de São Carlos, 2015)
The present work is part of the program Observatório da Educação funded by CAPES, INEP and SECADI. The referred program is integrated with a research project named Municipal Public Policies in Early Childhood Education: diagnosis and research. According to the Brazilian law 12.796/2013, school registration of children between four and five years old is mandatory. Therefore, the aim of this study was to verify if children under four years old are treated differently when enrolling in municipal schools for childhood education or schools that have a partnership with the government. We sought to identify the socioeconomic and racial profile of teachers and families served by municipal schools in São Carlos and to investigate how this profile is present in childcare centers and preschools. We used a survey with probability sampling to randomly select 1,300 children enrolled in public schools for early childhood education and conducted a census for the teachers on these schools. This investigation is relevant to the analysis of public policies because it is evaluative-diagnostic based. The results of this research support the idea that most parents declared their children as whiter when stating their race or color. We identified an underrepresentation of white children in childcare age when compared to their representation in the city population. We also observed that the geographical regions of Municipal School Supervision influence on racial distribution of children. Therefore, the presence of black children at schools located in peripheral regions is more frequent. It is apparent from the data collected that the older the teachers are, the whiter they are and, consequently, the younger they are, the more present color diversity is. These results indicate an inversion of colors in this segment. There was a marked difference between the socioeconomic profile of teachers and children. Interestingly, we noted that most children in preschool age are enrolled in public schools while children aged zero to three are prioritized in philanthropic institutions. This study has shown that there was an increase in children in preschool age per teacher in Municipal schools, exceeding the child-teacher ratio.
Keywords: Educação infantil; Políticas públicas; Diagnóstico; Indicadores; Public policies; Early childhood education; Diagnosis; Indicators; CIENCIAS HUMANAS::EDUCACAO